2020
DOI: 10.1055/s-0040-1710389
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Patients after Repair of Esophageal Atresia: A Review of Current Literature

Abstract: Patients born with esophageal atresia (EA) require advanced reconstructive surgery and risk long-term digestive and respiratory morbidity. We describe the state of current literature on these patients' health-related quality of life (HRQoL) and give recommendations for future research. A literature search was conducted in PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), and PsychINFO and included articles from 2015 to December 28, 2019. Criteria for selecting articles were predefined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 50 publications
2
33
0
Order By: Relevance
“…Other authors have already shown that long-term complications can sometimes only arise later in life; therefore, we cannot issue a final statement regarding long-term complications and HRQoL on our comparatively young patient cohort. 9,11,19,20,38,64,68 To solve this issue, longitudinal studies are warranted. These would allow changes in the prevalence of long-term complications and scores of HRQoL questionnaires to be recorded age dependently and compared at regular intervals.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have already shown that long-term complications can sometimes only arise later in life; therefore, we cannot issue a final statement regarding long-term complications and HRQoL on our comparatively young patient cohort. 9,11,19,20,38,64,68 To solve this issue, longitudinal studies are warranted. These would allow changes in the prevalence of long-term complications and scores of HRQoL questionnaires to be recorded age dependently and compared at regular intervals.…”
Section: Limitationsmentioning
confidence: 99%
“…14,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Various conditions (e.g., low birth weight, prematurity, pulmonary symptoms, feeding difficulties), treatment options (e.g., gastrostomy insertion, esophageal replacement), and long-term complications (e.g., anastomotic stenosis requiring recurrent dilatation) have been shown to restrict the QoL or HRQoL in patients with repaired EA. 31,32,37,38,41,42 In light of the fact that parents also have to bear part of the burden of their child's disease, the impact hereof on the parents' general well-being has not been studied well. 27,35 Considering the long-term complications frequently seen during outpatient visits, we assume a reduced HRQoL in patients with repaired EA and an impact on the parents' general well-being.…”
Section: Introductionmentioning
confidence: 99%
“…An elaborate review on the health-related quality of life (HrQOL) of patients born with esophageal atresia showed that these patients experience a lower quality of life as compared to their peers. [50]…”
Section: Long-term Effects Of the Repeated Hospitalization And Anesthesia Exposuresmentioning
confidence: 99%
“…Most research on long-term outcome of EA has focused on physical impairments or QOL, both in children and young adults. 5 , 6 A recent elaborate review on health related QOL (HrQOL) of patients born with EA concluded that clinical subgroups of children with EA present with impaired HrQOL, and that digestive symptomology negatively influences the HrQOL. 6 Neurodevelopment has been less well studied, and available studies reported conflicting results.…”
Section: Introductionmentioning
confidence: 99%